Exploring and Prioritizing Cultural Factors Affecting Knowledge Sharing in R&D Center of Petrochemical Industry - Masumeh Pahlevai; Reza Pirayesh; Vahideh Alipour; Mohammad Bashokouh (Journal of Information Technology Management)
This research aims at investigating the role of certain factors in organizational culture in the success of knowledge sharing. The research question asks which cultural factors affect knowledge sharing in R&D center of petrochemical industry. Research method used in research is survey. Of the 190 survey packages sent out, 132 of the questionnaires returned. To analyze data we use Spearman correlation and to prioritize the factors we use Fridman test. The results indicate that trust, communication between staff, information systems, rewards and organization structure play an important role in knowledge sharing.